Methods of drawing characters in the novels of Habib Abd al-Rab Sururi - Younis, Ayat; Mohsen , Carnival (Al-Adab Journal, 2024)
This work reveals three styles employed by Sarory in his novels: reporting style, pictorial style and deductive style. The writer excelled in using the characteristics every style to draw his characters and highlighting them and clarifying the general side of the novel and its artistic vision. The character in the novel is the major pivot in the narrative framework, as it promotes the events and delimit the affiliation of the narrative work. The novelist made them live, vibrant characters, and showed the outside and the inside and the intellectual perspectives, as they are more free in the pictorial style, as it permits them to present themselves, and the opposite is in the reporting style wherein the novelist controls them and restricts their freedom and draws their movements and emotions. Sarory is not satisfied with that, rather he dives into the secrets of itself to reveal its hidden vitality and passions and what goes on inside it through the deductive style. This work in divided into sections: theoretical and applied sides, to highlight the esthetics and significance of the character employed in the novel.